Stolica Apostolska w polskiej polityce zagranicznej na uchodźstwie (Wrzesień 1939 – czerwiec 1940) - Kornat, Marek (Polski Przegląd Stosunków Międzynarodowych, 2018)
The Holy See In Polish Foreign Policy of the Government on exile (September 1939 — June 1940) The article is devoted to the reexamining of the policy of Polish Government on exile toward the Holy See after Poland’s defeat in September 1939 and the reestablishment of the legal authorities of Poland in France, under President Raczkiewicz and General Sikorski as Prime Minister. Terminus ad quem of the narration is the collapse of France and transfer of the Government of Poland to London in June 1940. Problems of Vatican’s perception of Polish Question is discussed on the basis of Polish archival documents, especially those of Polish Embassy to the Holy See. Vatican-Polish relations at the beginning of the World War II require special attention because the last treatment of this highly debatable problem was made in historiography by Zofia Waszkiewicz more than thirty five years ago in her monograph Polityka Watykanu wobec Polski 1939–1945 [Policy of the Vatican toward Poland 1939—1945] (Warsaw 1980). How much Polish diplomacy achieved fighting for the Holy See’s support against Nazi Germany? Two things must be said. Firstly, the Holy See recognized the legal continuity of Polish State after the German-Soviet occupation of Poland’s territory in September 1939, but did not sent the papal nuncio to Angers, when Polish Government resided. Secondly, Polish thesis on the special significance of Polish Question as the test-case of international justice received the positive response of the Pope Pius XII in his encyclical Summi Pontificatus published on October 20 1939, but the guidelines of Vatican’s policy were based on the doctrine of strict neutrality of the Papacy in the international relations. It did not permit for Papal condemnation ex officio of the Nazi crimes and criminal policy of extermination in Poland.